\(C=\frac{98^{99}+1}{98^{89}+1}\)
\(D=\frac{98^{98}+1}{98^{88}+1}\)
\(C< \frac{98^{99}+1+97}{98^{89}+1+97}=\frac{98^{99}+98}{98^{89}+98}=\frac{98^{98}\left(98+1\right)}{98^{88}\left(98+1\right)}\)
\(C< \frac{98^{98}}{98^{88}}=D\)
\(C=\frac{98^{99}+1}{98^{89}+1}\)
\(D=\frac{98^{98}+1}{98^{88}+1}\)
\(C< \frac{98^{99}+1+97}{98^{89}+1+97}=\frac{98^{99}+98}{98^{89}+98}=\frac{98^{98}\left(98+1\right)}{98^{88}\left(98+1\right)}\)
\(C< \frac{98^{98}}{98^{88}}=D\)
So sánh :
C= \(\dfrac{98^{99}+1}{98^{89}+1}\) và D = \(\dfrac{98^{98}+1}{98^{88}+1}\)
So sánh : C = 9899+1/9889+1
D = 9898+1/9888+1
So sánh :C=98^99 +1/98^89 +1
vs
D=98^98 +1/98^88 +1
so sánh \(C=\frac{^{98^{99}}+1}{98^{89}+1}\)và D=98^98+1/98^88+1
khẩn cấp nhé
C=98^99+1/98^89+1 va D=98^98+1/98^88+1. So sanh C va D
C=98^99+1/98^89+1 va D=98^98+1/98^88+1. So sanh C va D
So sánh C=\(\frac{98^{99}+1}{98^{89}+1}\) và D=\(\frac{98^{98}+1}{98^{88}+1}\)
So sánh C=\(\frac{98^{99}+1}{98^{89}+1}\) và D=\(\frac{98^{98}+1}{98^{88}+1}\)
So sánh : C = 9899+1/9889+1
D = 9889+1/9888+1
Làm ơn giúp mình đi! Mình xin đấy. Sắp hế giờ rồi